The COVID-19 pandemic and mental health in Malaysia: Current treatment and future recommendations - Amoneeta Beckstein; Balan Rathakrishnan; Paul B. Hutchings; Noor Hassline Mohamed (Malaysian Journal of Public Health Medicine, 2021)
This paper provides an overview of Malaysian mental health in light of COVID-19. It discusses some of the current treatment options and how the crisis is being managed. A focused literature review was conducted. All relevant articles were included in the review. It offers research, policy, and multicultural practice suggestions for reducing the predicted upcoming mental health pandemic. There needs to be a multiculturally competent, multi-pronged public health strategy to address the psychological damage caused both during and after the pandemic. The government, health and mental health sectors, policymakers, and academic experts need to engage in a meaningful collaboration that leads to policies, resources, and actions to prevent future distress. This paper contributes to the knowledge about the mental health impact and response to the COVID-19 pandemic in a less studied country.